X-RAY COMPUTED TOMOGRAPHY APPARATUS AND IMAGE GENERATION METHOD (2022)
An X-ray computed tomography apparatus images a subject while relatively rotating an X-ray source and an X-ray detector, and the subject. The X-ray computed tomography apparatus includes a theoretical image calculation unit that calculates a theoretical image obtained by irradiating a test object for calibration with X-rays using a geometrical parameter indicating a positional relationship between the X-ray source and the X-ray detector, a correction amount calculation unit that calculates a correction amount based on an amount of deviation between the theoretical image of the test object for calibration and a fluoroscopic image obtained by irradiating the test object for calibration with X-rays, and an image correction unit that corrects a fluoroscopic image of the subject using the correction amount.